2013
DOI: 10.3109/17435390.2013.842266
|View full text |Cite
|
Sign up to set email alerts
|

Co-assessment of cell cycle and micronucleus frequencies demonstrates the influence of serum on thein vitrogenotoxic response to amorphous monodisperse silica nanoparticles of varying sizes

Abstract: Serum proteins have been shown to modulate the cytotoxic and genotoxic responses to nanomaterials. The aim was to investigate the influence of serum on the induction of micronuclei (MN) by nanoparticles (NPs) of different sizes. Therefore, A549 human lung carcinoma cells and amorphous monodisperse silica nanoparticles (SNPs) were used as models. Assessment of the cell viability, cell cycle changes and induction of MN by SNPs ranging from 12 to 174 nm was performed in presence or absence of serum, applying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Another relevant parameter which we studied is the effect of different serum concentrations. It was reported that the serum levels have an impact on the genotoxic and acute toxic properties of chemicals and nanoparticles by modulation of their bioavailability and/or alterations of the activity of drug metabolizing enzymes (Wiencke et al, ; Wang and Lee ; Gonzalez et al, ; Lubberstedt et al, ; Pisani et al, ). The serum effect was compound specific; it was observed with certain direct acting chemicals such as CDDP and Etop but not with other substances (MMS and H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant parameter which we studied is the effect of different serum concentrations. It was reported that the serum levels have an impact on the genotoxic and acute toxic properties of chemicals and nanoparticles by modulation of their bioavailability and/or alterations of the activity of drug metabolizing enzymes (Wiencke et al, ; Wang and Lee ; Gonzalez et al, ; Lubberstedt et al, ; Pisani et al, ). The serum effect was compound specific; it was observed with certain direct acting chemicals such as CDDP and Etop but not with other substances (MMS and H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by analysing the increase of the frequency of hypodiploid nuclei, the flow cytometer approach is sensitive not only to clastogens but also to aneuploidogens that interfere with the migration of chromosomes to spindle poles (20). This is important to analyse in a high-throughput manner since NM seem to exert their genotoxic potential also by mechanically interfering with the microtubules (21). Interestingly, recent studies on HepG2 cells exposed to silver nanoparticles (20 and 50nm) show not only an increase in MN frequency but also a dose-dependent increase in hypodiploid cells, thus suggesting involvement of aneugenicity (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus plausible interference and/or cross-talk between different dyes/ENMs could pose a challenge in the interpretation of MNi data sets. However, one way to correct for potential interferences is to simultaneously combine cell cycle data with MNi data to overrule inaccuracies in the evaluation of the genotoxic effects of ENMs (90). …”
Section: Introductionmentioning
confidence: 99%